The Effect of the 5E Learning Cycle Model on Student Learning Outcomes in Islamic Elementary School - Wulansari, Dista Suci; Adriyani, Zuanita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effect of the 5E learning cycle model on student learning outcomes in grade IV, especially on the material life cycle of living things. The effect of this study is shown by the difference in the average student learning outcomes of the experimental class and the control class. This research is quantitative research, with a quasi-experimental design with a posttest-only control design. The population in this study were all fourth-grade students at MI Nurul Islam, a total of 109 children. The sampling technique in this study used the Simple Random Sampling technique. It is said to be simple (simple) because the collection of sample members is done randomly without regard to the strata in the population. The sample in this study was class IVA which consisted of 28 students as the experimental class, and class IVD which consisted of 27 students as the control class. In data collection techniques, researchers used documentation, observations, and tests. In this study, researchers obtained primary data by means of interviews, observations, and tests. Meanwhile, researchers obtained secondary data from several relevant journals, books, and previous research. The data analysis technique used is to test (independent t-test). Based on the results of the t-test (independent t-test), the results obtained were Sig. (2-tailed) has a value of 0.000 <0.05, which means that there is an influence between the two variables. And the correlation/relationship (R) value is 0.875. From this output, the coefficient of determination (R Square) is 76.6%. This shows that the Learning Cycle 5E learning model influences student learning outcomes by contributing 76.6%, and the rest is influenced by other variables.